Exploring the Professional Development of Generation Z Teachers: A Qualitative Case Study on Enhancing Digital-Based Learning in Elementary Schools - Pradana, Arga; Santosa, Achadi Budi; Hidayati, Dian (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study explores the development of professionalism among Generation Z (Gen Z) teachers in enhancing the quality of digital-based learning in elementary schools. The research focuses on their adaptability, digital competence, and innovative teaching strategies in the context of rapidly evolving educational practices. Using a qualitative case study design, data were collected through in-depth interviews with Gen Z teachers at SD Muhammadiyah and analyzed to reveal patterns of digital pedagogy. The findings indicate that Gen Z teachers demonstrate strong digital literacy, actively employing interactive presentation applications, online learning platforms, and educational social media to enrich the learning process. Their professionalism is reflected in their commitment to self-directed learning, collaboration with colleagues, and reflective teaching practices. Supporting factors for professional development include institutional support, participation in teacher learning communities, and continuous training opportunities. However, challenges remain, particularly limited school facilities and students’ diverse adaptability to digital environments. This study contributes to the discourse on teacher professionalism by emphasizing the pivotal role of Gen Z teachers in advancing digital pedagogy. It concludes that Gen Z teachers possess considerable potential to improve learning quality through digital innovation, yet sustained institutional support is crucial to maximize their impact.